2006
DOI: 10.1021/es052010b
|View full text |Cite
|
Sign up to set email alerts
|

American Exceptionalism? Similarities and Differences in National Attitudes Toward Energy Policy and Global Warming

Abstract: Despite sharp differences in government policy, the views of the U.S. public on energy and global warming are remarkably similar to those in Sweden, Britain, and Japan. Americans do exhibit some differences, placing lower priority on the environment and global warming, and with fewer believing that "global warming has been established as a serious problem and immediate action is necessary". There also remains a small hard core of skeptics (<10%) who do not believe in the science of climate change and the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 8 publications
2
69
1
Order By: Relevance
“…In summary, there is a general concern that the public is not informed on CCS (also a conclusion made by Ramírez et al, 2008) which is also confirmed by polls on CCS (e.g. Reiner et al, 2006). Here, follow up studies on stakeholder and public attitudes are important to see if stakeholder concerns decrease and/or public knowledge increases over time.…”
Section: Q2 How Would You Characterize the Role That Ccs Plays In Thmentioning
confidence: 54%
See 2 more Smart Citations
“…In summary, there is a general concern that the public is not informed on CCS (also a conclusion made by Ramírez et al, 2008) which is also confirmed by polls on CCS (e.g. Reiner et al, 2006). Here, follow up studies on stakeholder and public attitudes are important to see if stakeholder concerns decrease and/or public knowledge increases over time.…”
Section: Q2 How Would You Characterize the Role That Ccs Plays In Thmentioning
confidence: 54%
“…Question Q4 did not relate the technologies to costs or ability to contribute to CO2 reductions which if included in question may of course have given a different picture. A previous study by the authors (Reiner et al 2006) polled the public in the same four regions as in this study. A majority of the public strongly preferred renewable-based technologies over fossil fuelled technologies and nuclear power.…”
Section: Q2 How Would You Characterize the Role That Ccs Plays In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…As an equivalent to 'stopping climate change' or 'solving global warming', this value is similar to the one implied by Viscusi & Zeckhauser (2006). In any case, our WTP-values are much lower than those in the study by Reiner et al (2006). Alavalapati et al (2004) investigated benefits for 3 environmental attributes (C-sequestration, water quality, wildlife habitats in silvopasture).…”
Section: Discussionmentioning
confidence: 61%
“…Viscusi & Zeckhauser (2006) found a mean WTP of 0.32 € per gallon of gas to eliminate the risks of climate change for a 30 yr period. Similarly, Reiner et al (2006) asked how much respondents would pay on top of their existing electric bill to 'solve global warming'; 90% of respondents were willing to pay a maximum of 32 € per month, (< 400 € yr -1 on US Department of Transportation 2008). This is much higher than the shadow price for the sequestration of 1 t C emitted in our results (7.34 € t C emitted person -1 yr -1) .…”
Section: Discussionmentioning
confidence: 99%